2022
DOI: 10.1186/s40677-022-00222-5
|View full text |Cite
|
Sign up to set email alerts
|

Successful emergency evacuation from a catastrophic loess landslide reactivated by the torrential rain in October 2021 in Tianshui, Ganusu, NW China

Abstract: Background At the beginning of October 2021, the northwest China suffered torrential rainfall and several loess landslides were induced in Northwest China. This work presents a typical case (the Zhongzhai landslide) reactivated during this period in Niangniangba town, Tianshui, Gansu, China. The retrogressive failure was triggered again in the early morning of 5 October 2021 after a succession of torrential rain, and buried 2 houses and damaged another 2 houses. In this work, the geometric feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Zhang et al . (2016) showed that the rate of this hourly precipitation data correctness at all stations is generally high.…”
Section: Methodsmentioning
confidence: 82%
See 2 more Smart Citations
“…Zhang et al . (2016) showed that the rate of this hourly precipitation data correctness at all stations is generally high.…”
Section: Methodsmentioning
confidence: 82%
“…The proportion of missing values at all stations was less than 7.7%, and approximately 98% of stations had less than 5% missing data (Figure S2c). Zhang et al (2016) showed that the rate of this hourly precipitation data correctness at all stations is generally high.…”
Section: Datamentioning
confidence: 81%
See 1 more Smart Citation
“…Hourly records from 303 gauge stations within the study region (96°–107°E and 21°–34°N, as shown in Figure 1) are used, to investigate the climatic characteristics of precipitation there during the period of 1995–2015 in summer (June–August). The data set is provided and quality‐controlled by the National Meteorological Information Center of the China Meteorological Administration (Zhang et al, 2016). The missing value is less than 10% of all records of each selected station during the study period.…”
Section: Study Region Data and Methodsmentioning
confidence: 99%
“…As the soil mass gradually reached saturation (Fig. 1), the anti-sliding force reduced while the sliding force increased, leading to the instability of the landslide mass (Zhang et al, 2022). Due to the vast uncertainty of natural slope materials, accurately quantifying the impact of rainfall on slope failures remains a major challenge, and physical model tests are still one of the most effective methods to study landslides.…”
Section: Introductionmentioning
confidence: 99%